La transparencia y el acceso a la información en la Administración Pública en el GAD cantonal de San Vicente - Vera Velásquez, María Victoria (2024)
The purpose of this research work was to determine the transparency and access to information of the cantonal GAD in San Vicente so that citizens are informed of the administrative management carried out by the government. For which methods such as inductive, deductive, analytical and synthetic were used; which were substantial for obtaining information regarding the problem. On the other hand, to collect data, an interview was conducted with the mayor of the canton, an instrument that allowed direct contact with the study variable. In this research, we worked with a sample of 375 citizens, to whom a survey was administered in person, which was structured based on the Likert scale, providing different response options; therefore, the result was that there is a deficit in the transparency processes and in addition, information on public affairs is not fully accessible to citizens. On the other hand, respondents revealed that the use of digital media is a complex issue, therefore, there is little importance for the data published on government websites. Furthermore, they state that the requests they make are not responded to within the established time.